Entrepreneurial orientation of rural women in the hill districts of Uttarakhand: a behavioural perspective. (9th September 2022) - Mishra, Amar Kumar; Nayak, Tapan Kumar; Upadhyay, Rajesh Kumar; Rai, Anjali
The Government of India in the last two decades has carved out many small regions from their parental states such as Chattisgarh, Jharkhand, Uttarakhand and recently Laddakh. These regions are full of natural resources, and the government had initiated and implemented various policies for their development. However, the results are a bit lopsided. The growth seems to be more skewed towards plain areas then hill areas. Even in the hill regions, it is more skewed towards urban districts then rural districts. And within the rural district, it is more skewed towards males than women. There is a very meagre change in the development of women in the rural areas of hill districts. This calls for a paradigm shift. This calls for a change from an agricultural society to an entrepreneurial society. However, entrepreneurship cannot be developed from outside unless there is an orientation from within. The purpose of this paper is to explore the entrepreneurial orientation among women in the rural regions of hill districts of Uttarakhand.